Two new Mycena (Mycenaceae, Agaricales) species with rhizomorphs from subtropical areas of China - Liu, Li-Na; Zhou, Guo-Ying; Tan, Zhu-Ming; Tian, Yong-Xiang (Phytotaxa, 2022)
Two new taxa are described from subtropical areas of China: Mycena chlorocyanea sp. nov. in sect. Viscipelles, and Mycena flosoides sp. nov. in sect. Polyadelphia. Photographs of basidiomata and morphological features, and relevant illustrations of these species are presented in this paper. Morphological characters were compared with related Mycena species, and phylogenetic analyses were conducted using internal transcribed spacer and the large subunit regions of nuclear ribosomal RNA gene sequences with Bayesian Inference and Maximum Likelihood. The phylogenetic trees showed that the two new taxa can be distinguished from phenotypically similar and phylogenetically related species.